2015
DOI: 10.1016/j.neuroscience.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Cross-frequency coupling in deep brain structures upon processing the painful sensory inputs

Abstract: Cross-frequency coupling has been shown to be functionally significant in cortical information processing, potentially serving as a mechanism for integrating functionally relevant regions in the brain. In this study, we evaluate the hypothesis that pain-related gamma oscillatory responses are coupled with low-frequency oscillations in the frontal lobe, amygdala and hippocampus, areas known to have roles in pain processing. We delivered painful laser pulses to random locations on the dorsal hand of five patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 104 publications
(144 reference statements)
1
16
0
Order By: Relevance
“…Gamma EEG oscillations that occur in the human cortex, hippocampal formation and amygdala may be related to theta rhythms through cross frequency coupling as the theta rhythm modulates the gamma rhythm during the formation of declarative memories and the response to stimuli of negative Valence, such as pain (Fell et al, 2003; Liu et al, 2015a,b). These stimuli evoke both theta and gamma frequency activity over central, parietoinsular and medial Frontal sites, which may be connected to the hippocampus through the entorhinal cortex (Van and Pandya, 1975a,b; Aggleton et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma EEG oscillations that occur in the human cortex, hippocampal formation and amygdala may be related to theta rhythms through cross frequency coupling as the theta rhythm modulates the gamma rhythm during the formation of declarative memories and the response to stimuli of negative Valence, such as pain (Fell et al, 2003; Liu et al, 2015a,b). These stimuli evoke both theta and gamma frequency activity over central, parietoinsular and medial Frontal sites, which may be connected to the hippocampus through the entorhinal cortex (Van and Pandya, 1975a,b; Aggleton et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies on gamma oscillations in experimental brief and tonic pain in healthy human beings and in normal rats (Croft et al, 2002; Gross et al, 2007; Wang et al, 2011; Hu et al, 2014; Liu et al, 2015b,a; Schulz et al, 2015; Li et al, 2016), as well as convert pain in patients with chronic disorders of consciousness (Naro et al, 2016), knowledge about the spontaneous and task-free gamma oscillatory activity in pathological, long-lasting chronic pain state are still in expectation. Our present study found that ECoG gamma activity increased under chronic inflammatory pain condition in a CFA monoarthritis model of rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that gamma band activation participates in pain perception. The power of gamma oscillations increases after brief nociceptive laser stimulations in healthy human beings (Gross et al, 2007; Tiemann et al, 2010; Schulz et al, 2011; Zhang et al, 2012; Hu et al, 2014; Liu et al, 2015a,b) and in normal rats (Wang et al, 2011), indicating that gamma oscillations are related to experimental acute pain lasting for milliseconds to seconds. Such gamma activity is focused on somatosensory cortex and positively correlated with the perceived pain intensity measured by the subjective rating of pain sensation on human beings (Gross et al, 2007; Zhang et al, 2012; Hu et al, 2014; Liu et al, 2015a) and with convert pain processing in patients with chronic disorders of consciousness (Naro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cross-frequency coupling has functional significance in cortical information processing, thereby contributing to the integration of relevant regions in the brain [ 68 ]. In human beings, painful laser stimulation enhance gamma oscillatory responses in the pain-related amygdala and hippocampal regions, and these gamma responses are significantly coupled with the phases of theta and alpha rhythms during pain processing [ 69 ]. Painful cutaneous laser stimuli also induce event-related gamma band activity in the lateral thalamus in humans, and thalamic cross-frequency coupling analysis indicates that the phase of the lower frequency activity (theta to beta) modulates the amplitude of the higher frequency activity (low and high gamma) more strongly during the cutaneous laser stimuli [ 70 ].…”
Section: Discussionmentioning
confidence: 99%